A method for acoustic storage pest detection and its challenges - Christina Müller-Blenkle; Ulrich Simon; Ralf Meyer; Isabell Szallies; Daniela Lorenz; Sabine Prozell; Matthias Schöller; Cornel S. Adler (Journal für Kulturpflanzen, 2023)
Insects in grain can cause serious problems, not only because they feed on the grains. Mass reproduction also causes additional moisture and heat due to the insects' metabolism. This leads to favourable conditions for moulds, which can cause major losses and the formation of mycotoxins. It is therefore important to detect and treat an infestation at an early stage. The "Beetle Sound Tube" system was developed as an acoustic early detection system for insects in grain, which makes it possible to detect even very low levels of infestation and inform the storekeeper by e-mail. The acoustic system remains in the grain during the storage period, and permanently records insect sounds. Challenges were encountered in the development of this acoustic monitoring system, such as analysing very quiet insect sounds in a noisy agricultural environment. In addition, the amount of data collected and the speed of analysis had to be optimised to achieve just-in-time detection of insects. The acoustic tube system was developed for silos, flat stores and big bags and is therefore widely applicable.